The Learned Eye : Regarding Art, Theory, and the Artist's Reputation - Doel, Marieke van den (Rembrandt, 2005)
Rembrandt and Rhetoric. The Concepts of affectus, enargeia and ornatus in Samuel van Hoogstraten's Judgement of His MasterPart III: The Artist's Reputation; 'A Record and Memorial of his Talents for Posterity': Anthony van Dyck's Sketch of the Garter Procession; 'Das Werk erdacht und cirkulirt'. The Position of Architects at the Court of King Ferdinand I of Bohemia and His Son, Archduke Ferdinand II of Austria; Crossing the Wall of History. Etienne Deléc